"THE DETAILED IMPACT OF ACCOUNTS RECEIVABLE BALANCES ON PROFIT MANAGEMENT INDICATIONS AT PT FORTUNE INDONESIA TBK FOR THE PERIOD 2021–2024" - Windy Indriyani; Diana Dewi; Nurul Adhani Ilham; Nurul Shofiyah; Sri Nurdewi Sartika Astuti (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the impact of detailed accounts receivable balances on indications of earnings management practices at PT Fortune Indonesia Tbk during the 2021–2024 period. The main focus of the study is to evaluate the role of accounts receivable and allowance for doubtful accounts as potential instruments in accrual-based earnings management practices. The method used is a descriptive quantitative approach utilizing secondary data from the company's financial statements. The analytical techniques applied include calculating the accounts receivable-to-revenue ratio and the allowance for doubtful accounts to gross receivables ratio, accompanied by observations of fluctuation trends from year to year. The results show significant fluctuations in both ratios, including the write-off of receivables without allowance in 2024. These findings indicate potential earnings management practices, especially in the 2022 and 2024 periods, through a disproportionate decrease in allowance for doubtful accounts and accelerated recognition of credit revenue. Thus, detailed accounts receivable can be an important indicator in detecting manipulative practices in financial statements, as well as providing input for auditors to focus on detailed audits of accounts receivable balances.